Tripalmitin nanoparticle formulations significantly enhance paclitaxel antitumor activity against breast and lung cancer cells in vitro. Issue 1 (December 2017) - Leiva, María; Ortiz, Raúl; Contreras-Cáceres, Rafael; Perazzoli, Gloria; Mayevych, Iryna; López-Romero, Juan; Sarabia, Francisco; Baeyens, Jose; Melguizo, Consolación; Prados, Jose
Abstract Paclitaxel (PTX) is one of the drugs of choice in the treatment of breast and lung cancer. However, its severe side effects, including mielosuppression, cardiotoxicity and neurotoxicity, frequently cause treatment to be discontinued. Solid lipid nanoparticles (NPs) of glyceril tripalmitate (tripalmitin) loaded with PTX (Tripalm-NPs-PTX) including modifications by the addition of hexa(ethylene glycol), β-cyclodextrin and macelignan were developed. All NPs-PTX formulations displayed excellent hemocompatibility and significantly enhanced PTX antitumor activity in human breast (MCF7, MDAMB231, SKBR3 and T47D) and lung (A549, NCI-H520 and NCI-H460) cancer cells. Tripalm-NPs-PTX decreased PTX IC50 by as much as 40.5-fold in breast and 38.8-fold in lung cancer cells and Tripalm-NPs-PTX macelignan inhibited P-glycoprotein in resistant tumor cells. In addition, Tripalm-NPs-PTX significantly decreased the volume of breast and lung multicellular tumor spheroids that mimicsin vivo tumor mass. Finally, Tripalm-NPs-PTX decreased the PTX IC50 of cancer stem cells (CSCs) derived from both lung and breast cancer cells (6.7- and 14.9-fold for MCF7 and A549 CSCs, respectively). These results offer a new PTX nanoformulation based on the use of tripalmitin which improves the antitumor activity of PTX and that may serve as an alternative PTX delivery system in breast and lung cancer treatment.